Incidence of cytopathological changes in patients attended by the brazilian Public Health System (SUS) in the central region of Rio Grande do Sul: analysis of cervical cancer screening - Mertins, Hellen Lucas; Guterres, Isabela Scheffer; Birrer, Caroline Arend; Ziani, Jarbas da Silva; Santos, Mylane Genro; da Silva, Gabriela Pozzobon Zamberlan; de Oliveira, Renata Casarotto; Monteiro, Francielle Liz (Disciplinarum Scientia | Saúde, 2025)
Cervical cancer is one of the leading causes of morbidity and mortality among women in Brazil and can be prevented through HPV vaccination and cytopathological screening. This study aimed to determine the incidence of cytopathological changes in women treated by the SUS in the central region of Rio Grande do Sul. This is a quantitative, retrospective, and analytical study using data from cytopathological exams performed between January 2022 and July 2023 in 22 municipalities in the central region. During this period, 28,524 Pap smear tests were performed, with an average coverage rate of 23.2 %. Of these exams, 2.5 % showed cervical lesions, with ASC-US being the most frequent lesion (36.7 %), followed by LSIL (21.5 %) and HSIL (11.9 %). The highest incidence of lesions was observed in the age groups of 45 to 54 years (26.0 %), 35 to 44 years (23.9%), and 25 to 34 years (22.8 %). Most lesions (85.1 %) occurred in women aged 25 to 64 years - the age group recommended for the test. The analysis revealed significant variations in coverage among the municipalities. The highest incidence of cervical lesions occurred in the 45 to 54 age group, coinciding with greater adherence to the exam. The results highlight the need to expand public health policies, intensify educational campaigns, strengthen HPV vaccination, and address inequalities in access to healthcare services.